Overview of the legal, institutional and regulatory framework relating to privatized utilities : on making natural monopoly compatible with competitiveness - Odle, Maurice A. ([s.n.] [S.l.], 1995)
Shows how for successful privatization of public utilities to take place the legislative institutional and regulatory framework must play an important role.